THE DEGREE OF AVAILABILITY OF LEARNING ORGANIZATION CONTROLS FOR SENGE IN IRBID UNIVERSITY COLLEGE FROM THE POINT OF VIEW OF EMPLOYEES: OBSTACLES AND DEVELOPMENT PROPOSALS - Shoqran, Abdullah Abd El Karim Al (European Scientific Journal, ESJ, 2013)
This study aimed to identify the degree of availability of Senge’s controls of the learning organization in Irbid University College from the employees’ perspective, as well as to clarify the major obstacles and proposals that limit the degree of availability of such controls. The population of the study consisted of all staff in Irbid University College, the sample of the study consisted of (186) member, a questionnaire consisted of (56) items and two open questions were designed in order to achieve the objectives of the study. The conclousion of the study revealed that the degree of availability of Senge’s controls of the learning organization in Irbid University College was medium, and there were not statistically significant differences attributed to gender variable, while there were statistically significant differences attributed to the variables of profession and years of experience. The most frequent obstacles are: lack of adequate infrastructure, lack of adequate financial support for the application of Senge’s controls of the learning organization. While the most frequent recommendations are: the provision of financial support that commensurate with the practice of the controls of learning organization, and change of the traditional administrative styles to modern patterns that are consistent with the application of learning organization